Genomic characterization of tigecycline-resistant Escherichia coli and Klebsiella pneumoniae isolates from hospital sewage - Li, Ying; Fu, Yu; Qiu, Yichuan; Liu, Qian; Yin, Ming; Zhang, Luhua (Frontiers in Microbiology, 2023)
The tigecycline-resistant Enterobacteriaceae Enterobacterales have emerged as a great public concern, and the mobile tet(X) variants and tmexCD-toprJ efflux pump are mainly responsible for the spread of tigecycline resistance. Hospital sewage is considered as an important reservoir of antimicrobial resistance, while tigecycline resistance in this niche is under-researched. In this study, five Escherichia coli and six Klebsiella pneumoniae strains were selected from a collection of tigecycline-resistant Enterobacteriaceae Enterobacterales for further investigation by antimicrobial susceptibility testing, conjugation, whole-genome sequencing, and bioinformatics analysis. All five E. coli strains harbored tet(X4), which was located on different plasmids, including a novel IncC/IncFIA(HI1)/IncHI1A/IncHI1B(R27) hybrid structure. In addition, tet(X4)-bearing plasmids were able to transfer by conjugation and be stabilized in the recipient in the absence of antibiotics. tmexCD1-toprJ1 was identified in two K. pneumoniae (LZSFT39 and LZSRT3) and, especially, it was carried by a novel multidrug-resistance transposon, designated Tn7368, on a novel IncR/IncU hybrid plasmid. In addition, we found that two K. pneumoniae (LZSFZT3 and LZSRT3) possessshowed overexpression of efflux genes acrB and oqxB, respectively, which was most likely to be caused by mutations in ramR and oqxR. In conclusion, The the findings in this study expand our knowledge of the genetic elements that carry tigecycline resistance genes, which establishes a baseline for investigating the structure diversity and evolutionary trajectories of human, animal, and environmental tigecycline resistomes. of novel genetic elements that carry tigecycline resistance genes highlight the vital role of hospital sewage as a potential reservoir of drug-resistance bacteria and their transmission of antimicrobial resistance through the water environment. Continuous monitoring of environmental bacteria possessing tigecycline resistance would help us to better control its dissemination.